SOI MOS Technology for Spin Qubits. (22nd October 2019) - Hutin, Louis; Bertrand, Benoit; Niquet, Yann-Michel; Hartmann, Jean-Michel; Sanquer, Marc; De Franceschi, Silvano; Meunier, Tristan; Vinet, Maud
Abstract : We fabricated Si Quantum Dot (QD) devices using relatively minor adaptations of a standard SOI CMOS process flow. We demonstrated that the spin of confined charges could be controlled via a local electrical-field excitation, owing in the caseof electrons to a geometrically-enabled tuning of the valley splitting and inter-valley spin-orbit coupling. We discuss improvement paths such as extending the spin coherence time by using epi-layers of nuclear-spin-free 28 Si (99.992%) as a device template, and developing novel 3D architectures compatible with topological quantum error correction schemes.